Transesophageal echocardiography in minimally invasive cardiac surgery. Issue 1 (February 2020) - Prempeh, Agya B.A.; Scherman, Jacques; Swanevelder, Justiaan L.
Abstract : Purpose of review: Transesophageal echocardiography (TEE) has made its way into the cardiac surgery realm and spurred the development of many interventions. In the domain of minimally invasive cardiac surgery (MICS), TEE has become central to reducing cardiovascular complications. Recent findings: Real-time three-dimensional TEE is a key contributor to the safe and precise deployment of the PASCAL mitral valve repair system, which is showing great potential in ongoing studies. The current data on outcomes of transcatheter aortic valve replacement show that preprocedural three-dimensional TEE and multidetector computed tomography (CT) perform similarly in aortic root assessment. Three-dimensional color Doppler TEE has been suggested to be more appropriate in quantifying residual mitral regurgitation and evaluating the success of surgical or percutaneous closure. A three-dimensional TEE-derived aortomitral angle may be valuable in predicting and detecting dynamic left ventricular outflow tract obstruction, thereby enhancing the safety of transcatheter mitral valve replacement. Summary: Advanced imaging modalities are essential for the sustained growth of MICS, particularly with the evolution of novel transcatheter systems. These techniques rely on exceptional imaging quality at all stages of the perioperative period to modify surgical-risk and improve patient outcomes. TEE has the additional benefit of providing real-time information on intrathoracic structures to guide intraoperative management. Abstract : Supplemental Digital Content is available in the text